Rancangan Infrastruktur Pembelajaran E-Learning dengan Teori Sistem Komunikasi Radio Gelombang Micro pada Wilayah Blank Spot Internet - Liesnaningsih, Liesnaningsih; Kasoni, Dian; Mulyati, Sri (Universitas Muhammadiyah Tangerang, 2024)
At the beginning of 2020, the education system in Indonesia evolved, this was the impact of the WHO (World Health Organization) statement regarding COVID-19 where WHO officially announced that COVID-19 was declared a global pandemic which resulted in schools being closed and replaced with distance or online learning. The implementation of distance or online learning has apparently encountered problems with internet signal coverage which is not evenly distributed throughout Indonesia, which makes it difficult for students, especially in rural areas. To deal with this problem, an e-learning system infrastructure design was created that does not use the internet network in the process. In the design process there are procedures or steps that will be taken, namely designing a wireless radio communication system to determine the radio wave signal transmission path that will send data from the transmitter to the receiver and vice versa using radio communication system theory to obtain LOS (Line Of Sight) or an unobstructed line of sight that takes into account the curvature of the earth, radio frequency link budget, and the reliability of the wireless radio communication system and also determines the estimated costs incurred to build an e-learning learning system infrastructure without the internet.Keywords: E-learning,Wireless Radio Communication System, LOS (Line of Sight)